1973
DOI: 10.1113/jphysiol.1973.sp010353
|View full text |Cite
|
Sign up to set email alerts
|

Presbyopia and the water content of the human crystalline lens

Abstract: SUMMARY1. The water content of the human crystallaline lens nucleus is 63-4 % S.D.±+2'9%, and cortex 68.6% S.D. + 4.30/.2. Neither the total water content of the cortex, nor that of the nucleus show any significant changes with age, so 'sclerosis' of the lens due to loss of water is not a cause of presbyopia.3. The initial loss of water from the nucleus of the lens substance obtained by drying in vacuo at 200 C for 2 hr is related to age (P = 0.05) and deformability (0.02 > P > 0.01).4. The lens fibres of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0
3

Year Published

1977
1977
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 2 publications
(3 reference statements)
6
44
0
3
Order By: Relevance
“…With age, the lens changes in size and in elastic properties [34, 35, 62, 63, 64, 65, 66], the choroid changes in elastic properties [66, 67], the ciliary muscle shows hypertrophic changes [68]and loss of elastic tissue at its choroidal attachment [69]while the elastic properties of the zonules do not change [65, 66]. …”
Section: Presbyopiamentioning
confidence: 99%
“…With age, the lens changes in size and in elastic properties [34, 35, 62, 63, 64, 65, 66], the choroid changes in elastic properties [66, 67], the ciliary muscle shows hypertrophic changes [68]and loss of elastic tissue at its choroidal attachment [69]while the elastic properties of the zonules do not change [65, 66]. …”
Section: Presbyopiamentioning
confidence: 99%
“…Fisher & Pettet (1973) showed that there is no loss of water in the presbyopic lens, but only a closer packing of fibres within the ageing lens nucleus which may cause a rise in its Young's modulus of elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns autores relataram frações relativamente fixas quanto ao peso líquido do cristalino, em amostras cujas idades oscilaram de 2,5 a 89 anos (4,11,13) ; outros estudos, porém, sugerem evidências de um aumento contínuo e gradativo na gravidade específica após o nascimento, indicando desidratação pequena, mas estável, de todo o cristalino, levando à afirmação de que, da vida fetal à vida adulta, há redução do volume ocupado pelo cristalino no globo ocular (1,9,(14)(15) .…”
Section: N T R O D U ç ã Ounclassified